Multi-sized microelectrode array coupled with micro-electroporation for effective recording of intracellular action potential - Xingyuan Xu; Zhengjie Liu; Jing Liu; Chuanjie Yao; Xi Chen; Xinshuo Huang; Shuang Huang; Peng Shi; Mingqiang Li; Li Wang; Yu Tao; Hui-jiuan Chen; et al. (Microsystems & Nanoengineering)
Abstract Microelectrode arrays (MEAs) are essential tools for studying the extracellular electrophysiology of cardiomyocytes in a multi-channel format. However, they typically lack the capability to record intracellular action potentials (APs). Recent studies have relied on costly fabrication of high-resolution microelectrodes combined with electroporation for intracellular recordings, but the impact of microelectrode size on micro-electroporation and the quality of intracellular signal acquisition has yet to be explored. Understanding these effects could facilitate the design of microelectrodes of various sizes to enable lower-cost manufacturing processes. In this study, we investigated the influence of microelectrode size on intracellular AP parameters and recording metrics post-micro-electroporation through simulations and experiments. We fabricated microelectrodes of different sizes using standard photolithography techniques to record cardiomyocyte APs from various culture environments with coupled micro-electroporation. Our findings indicate that larger microelectrodes generally recorded electrophysiological signals with higher amplitude and better signal-to-noise ratios, while smaller electrodes exhibited higher perforation efficiency, AP duration, and single-cell signal ratios. This work demonstrates that the micro-electroporation technique can be applied to larger microelectrodes for intracellular recordings, rather than being limited to high-resolution designs. This approach may provide new opportunities for fabricating microelectrodes using alternative low-cost manufacturing techniques for high-quality intracellular AP recordings.